Intercalation Na-ion storage in two-dimensional MoS2-xSex and capacity enhancement by selenium substitution - Jia, Guichong (2019)
Two-dimensional (2D) layered transition-metal dichalcogenides has been regarded as highly promising electrode materials for fast-rate Li-ion and Na-ion batteries. Monolayer or multilayer MoS2 nanoflakes have been employed for metal ion batteries, but the material suffers from poor cyclic stability due to damage of the layered structure in a decomposition reaction. Herein, we synthesize ultrathin MoS2-xSex nanoflakes quasivertically aligned on the graphene-like carbon foam (the obtained material is referred to as MoS2-xSex/GF) and investigate the Na-ion storage property using in-situ Raman spectroscopy and ex-situ XRD measurements. We show that by choosing appropriate potential range, it is possible to maintain the 2D layered structure and thus significantly improve the capacity retention due to the intercalation mechanism. As a freestanding electrode, the MoS2-xSex/GF demonstrates high-rate reversible Na-ion storage, where both the capacity and rate-performance are enhanced by the selenium substitution. This study sheds new light on better understanding of the metal ion storage mechanism of 2D transition metal chalcogenides that are being widely investigated.